Physical performance reference values for Japanese oldest old: a SONIC study - Matsumoto, Kiyoaki; Gondo, Yasuyuki; Masui, Yukie; Yasumoto, Saori; Yoshida, Yuko; Ikebe, Kazunori; Arai, Yasumichi; Kabayama, Mai; Kamide, Kei; Akasaka, Hiroshi; Ishizaki, Tatsuro (BMC geriatrics, 2022)
Background The oldest old, defined as those aged 90 or over, is now the fastest-growing population sector. This study aimed to determine reference values for several physical performance measures (PPMs) among 90-year-olds using internationally standardized measurements and to clarify the characteristics of these indices by comparing their results for 90-year-olds with those for older people 70 and 80. Methods We used the Septuagenarians, Octogenarians, and Nonagenarians Investigation with Centenarians (SONIC) study data from 2010 to 2018. The study subjects were 70, 80, and 90-year-olds in the target area eligible to participate in the venue. Excluding those certified for long-term care, the final number of eligible persons is 70s cohort 1000 (2010), 80s cohort 973 (2011), and 90s cohort 690. 90s cohort only consisted of three survey waves: 2012, 2015, and 2018. We used hand grip strength and score on the Short Physical Performance Battery (SPPB) for our physical performance measurements. In addition, we statistically analyzed sex and age differences. Result The simple mean ± standard deviation (SD) for the 90-year-old respondents were in men, 24.1 ± 5.4 kg in hand grip strength, 0.80 ± 0.22 m/s in usual gait speed, 17.2 ± 6.73 s in 5times chair stand, 5.89 ± 4.42 s in tandem balance, and 8.3 ± 2.2 in SPPB respectively and in women, 14.4 ± 4.0 kg in hand grip strength, 0.72 ± 0.20 m/s in usual gait speed, 17.8 ± 7.89 s in 5times chair stand, 4.72 ± 4.35 s in tandem balance, and 7.5 ± 2.4 in SPPB, respectively. For all PPMs, the age 90 cohort was statistically significantly different from the age 70 and 80 cohorts (all trends P <  0.001). Hand grip strength decreased with a similar gradient with age cohort increase of 10 years for both sexes. In contrast, SPPB lower limb score showed a larger drop between the age 80 and 90 cohorts than between the age 70 and 80 cohorts. We also constructed sex-specific appraisal standards according to quintiles. Conclusions Our study yielded inclusive sex-specific reference values and appraisal standards for major physical performance measures not certified as requiring long-term care, community-dwelling, oldest old Japanese. The characteristics of age-related decline in physical performance differed between the upper and lower extremity assessments.